Students’ Perceptions of the Academic Advising System (SPAk) at Kolej Komuniti Masjid Tanah - Abdullah, H.; Sajat, T. F.; Abdul Malik, N.; Faruq , A. (Politeknik & Kolej Komuniti Journal of Social Sciences and Humanities, 2026)
The Academic Advising System (SPAk) plays a vital role in supporting students' academic development and enhancing academic advising practices in Malaysian higher education institutions. However, empirical evidence on students' perceptions of SPAk implementation in community colleges remains limited. This study examined students' perceptions of SPAk implementation at Kolej Komuniti Masjid Tanah (KKMT), focusing on the roles and responsibilities of Academic Advisors and the effectiveness of the system across academic programmes. A quantitative descriptive research design was employed involving 202 students selected through stratified random sampling from four academic programmes. Data were collected using a structured questionnaire based on the SPAk Guidelines issued by the Ministry of Higher Education Malaysia and adapted from a validated instrument. The instrument demonstrated excellent internal consistency (Cronbach's Alpha = 0.982). Data were analysed using descriptive statistics, one-way Analysis of Variance (ANOVA), and Tukey's Honestly Significant Difference (HSD) test. The findings showed that students generally held positive perceptions of SPAk implementation (M = 4.47, SD = 0.58). No statistically significant differences were found in students' perceptions of the roles and responsibilities of Academic Advisors (F = 1.457, p = .228) or the effectiveness of SPAk implementation (F = 1.517, p = .211) across academic programmes, indicating consistent implementation of SPAk. This study contributes empirical evidence on academic advising in Malaysian community colleges and provides practical implications for the Department of Polytechnic and Community College Education (JPPKK) and community colleges to strengthen SPAk through continuous professional development, systematic monitoring, and integrated digital advising-systems.